Exogenous Ketones Lower Post-exercise Acyl-Ghrelin and GLP-1 but Do Not Impact Ad libitum Energy Intake - Okada, Tetsuro E.; Quan, Tony; Bomhof, Marc R. (Frontiers in Nutrition, 2021)
Ketosis and exercise are both associated with alterations in perceived appetite and modification of appetite-regulating hormones. This study utilized a ketone ester (R)-3-hydroxybutyl (R)-3-hydroxybutyrate (KE) to examine the impact of elevated ketone body D-β-hydroxybutyrate (βHB) during and after a bout of exercise on appetite-related hormones, appetite perception, and ad libitum energy intake over a two hour post-exercise period. In a randomized crossover trial, thirteen healthy males and females (age: 23.6 ± 2.4 years; body mass index: 25.7 ± 3.2 kg·m-2) completed an exercise session @ 70% VO2peak for 60 min on a cycling ergometer and consumed either: 1) Ketone monoester (KET) (0.5g·kg-1 pre-exercise + 0.25g·kg-1 post-exercise); or 2) isocaloric dextrose control (DEX). Transient ketonaemia was achieved with βHB concentrations reaching 5.0mM (range 4.1-6.1mM) during the post-exercise period. Relative to the dextrose condition, acyl-ghrelin (P = 0.002) and glucagon-like peptide-1 (P = 0.038) were both reduced by acute ketosis immediately following exercise. AUC for acyl-ghrelin was lower in KET compared to DEX (P = 0.001), however there were no differences in AUC for GLP-1 (P = 0.221) or PYY (P = 0.654). Perceived appetite (hunger, P = 0.388; satisfaction, P = 0.082; prospective food consumption, P = 0.254; fullness, P = 0.282) and 2 hr post-exercise ad libitum energy intake (P = 0.488) was not altered by exogenous ketosis. Although KE modifies homeostatic regulators of appetite, it does not appear that KE acutely alters energy intake during the post-exercise period in healthy adults.